Do mental health professionals use diagnostic classifications the way we think they do? A global survey. Issue 2 (June 2018) - First, Michael B.; Rebello, Tahilia J.; Keeley, Jared W.; Bhargava, Rachna; Dai, Yunfei; Kulygina, Maya; Matsumoto, Chihiro; Robles, Rebeca; Stona, Anne‐Claire; Reed, Geoffrey M.
Abstract : We report on a global survey of diagnosing mental health professionals, primarily psychiatrists, conducted as a part of the development of the ICD‐11 mental and behavioural disorders classification. The survey assessed these professionals' use of various components of the ICD‐10 and the DSM, their attitudes concerning the utility of these systems, and usage of "residual" (i.e., "other" or "unspecified") categories. In previous surveys, most mental health professionals reported they often use a formal classification system in everyday clinical work, but very little is known about precisely how they are using those systems. For example, it has been suggested that most clinicians employ only the diagnostic labels or codes from the ICD‐10 in order to meet administrative requirements. The present survey was conducted with clinicians who were members of the Global Clinical Practice Network (GCPN), established by the World Health Organization as a tool for global participation in ICD‐11 field studies. A total of 1, 764 GCPN members from 92 countries completed the survey, with 1, 335 answering the questions with reference to the ICD‐10 and 429 to the DSM (DSM‐IV, DSM‐IV‐TR or DSM‐5). The most frequent reported use of the classification systems was for administrative or billing purposes, with 68.1% reporting often or routinely using them for that purpose. A bit more than half (57.4%) of respondents reported often or routinely going through diagnostic guidelines or criteria systematically to determine whether they apply to individual patients. Although ICD‐10 users were more likely than DSM‐5 users to utilize the classification for administrative purposes, other differences were either slight or not significant. Both classifications were rated to be most useful for assigning a diagnosis, communicating with other health care professionals and teaching, and least useful for treatment selection and determining prognosis. ICD‐10 was rated more useful than DSM‐5 for administrative purposes. A majority of clinicians reported using "residual" categories at least sometimes, with around 12% of ICD‐10 users and 19% of DSM users employing them often or routinely, most commonly for clinical presentations that do not conform to a specific diagnostic category or when there is insufficient information to make a more specific diagnosis. These results provide the most comprehensive available information about the use of diagnostic classifications of mental disorders in ordinary clinical practice.